Performance Assessment Using Key Performance Indicators: A Case Study on Employee Assessment at CV Pustaka Tiga Mandiri: english - Raziki Waldan (Program Studi Manajemen Bisnis Syariah, 2024)
This study aims to evaluate the effectiveness of the Key Performance Indicators (KPI) method in assessing employee performance at CV Pustaka Tiga Mandiri. The research utilizes a qualitative approach with interviews, observations, and documentation as the primary data collection instruments. Employee performance evaluations at this company heavily depend on achieving targets set through KPIs, which serve as benchmarks for the success of individuals and departments in reaching the company’s strategic goals. The findings indicate that the implementation of KPIs at CV Pustaka Tiga Mandiri has a significant impact on employee performance, particularly in the marketing department. Employees who meet their targets receive better performance evaluations and additional incentives, while those who fail to do so are issued warnings to improve their performance. Performance evaluations also affect compensation, with salary deductions applied to employees who are absent without valid reasons. The implications of this study highlight the importance of implementing an objective and data-driven performance appraisal system to enhance productivity and efficiency within the organization. The study also demonstrates that using KPIs as an evaluation tool can help the company identify areas needing improvement and provide a solid foundation for managerial decision-making. The originality or novelty of this research lies in the application and evaluation of the KPI method within the context of a local company, which is still relatively uncommon in Indonesia. This study contributes to the understanding of how KPIs can be effectively used to improve employee performance in medium-sized enterprises.